Literature Review: Characteristics Of Patients With Osteoarthritis Genu - Nurfaizah Dido; Andi Dhedie Prasatia Sam; Muh Akram Chalid (Jurnal EduHealth, 2025)
Osteoarthritis gentle is one of the degenerative diseases that often occurs in the elderly population, characteristics by progressive damage to the knee joint cartilage that causes pain, limited mobility, and decreased quality of life. This study aims to analyze the characteristics of osteoarthritis gentle patients, including demographic profiles, risk factors, severity, and selected treatment patterns, in order to provide more effective intervention recommendations. The method used is a literature review by collect and analyzing various previous studies related to osteoarthritis gentle, especially those discussing risk factors, treatment patterns, and health service challenges. The results of the study showed that the majority of patients were postmenopausal women with high levels of obesity, low physical activity, and a history of joint injury. Many patients are late in accessing medical treatment and rely on alternative therapies that have not been proven effective. This study highlights the importance of public education, increasing access to health services, and more targeted health policies to prevent and treat osteoarthritis gentle optimally.